Interactive PnP innovation for Muamalat Diploma Students' Final Year Project - Yusoff, Nor Adila Mohd Noor; Ismail, Che Zuina; Muhammad, Hamizah; Yahaya, Salimah; Awang, Azarudin (Academica Press Solutions, 2023)
The Scientific paper is a required subject for final year Muamalat Diploma students at UiTMCTKD in semester 5. The Wheel of Fortune Interactive PnP Innovation Project (PWoFKi) method is used to assess students' comprehension of input for writing a scientific paper or research paper that was given in the form of a lecture during a scientific paper writing workshop held prior to students registering for this subject. This strategy was developed to encourage students to be more enthusiastic about comprehending all of the critical procedures involved in producing scientific articles without becoming bored, stiff, or passive in response to the feedback provided. The employment of (PWoFKi), which employs an intriguing gaming method, can be studied as a teaching and learning mechanism (PnP) in promoting learning delight. As a result, the goal of this study is to assess students' understanding of the appropriateness of using PWoFKi in the PnP process for the subject of Scientific Papers (IMU304), as well as to pique students' interest in the subject of Scientific Papers (IMU304), in order to improve the learning and teaching environment. A questionnaire was provided to 57 participants in a pilot research. To assess students' perceptions of implementation, data was analysed using SPSS 24 and compared to the mean score (PWoFKi). The results show that the mean score is 4.26 on a 5-point scale. This suggests that the innovation of usage (PWoFKi) in PnP topic IMU 304 can solve the problem of boredom while also making students have fun and improving their knowledge of the learning delivered. One of the games that may be used to interact and communicate for learning goals is the PWoFKi technique. The study's findings indicate that the PWoFKi method is a novel strategy in the IMU304 PnP process that can be used by any students pursuing Diploma, Degree, Masters, or Doctorate degrees in any public or private higher education institution.